2019
DOI: 10.1038/s41598-019-43767-6
|View full text |Cite
|
Sign up to set email alerts
|

TET1 contributes to allergic airway inflammation and regulates interferon and aryl hydrocarbon receptor signaling pathways in bronchial epithelial cells

Abstract: Previous studies have suggested a role for Tet1 in the pathogenesis of childhood asthma. However, how Tet1 contributes to asthma remains unknown. Here we used mice deficient for Tet1 in a well-established model of allergic airway inflammation and demonstrated that loss of Tet1 increased disease severity including airway hyperresponsiveness and lung eosinophilia. Increased expression of Muc5ac , Il1 3 , Il33 , Il … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
45
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 102 publications
9
45
0
Order By: Relevance
“…Our present study shows TET1-deficient moDCs suppressed conversion of naïve T cells into aTregs, the activated subset of regulatory T cells and are essential in maintaining immune tolerance and immune homeostasis, especially in those with AR (30). Recently, Burleson et al (43) established that HDM-challenged TET1-deficient mice have impaired interferon pathway, increased airway hyperresponsiveness, and eosinophilic infiltration in the lung. Together, this evidence suggests that the loss of TET1 induces the maturation of DCs and mediates the development of allergic airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Our present study shows TET1-deficient moDCs suppressed conversion of naïve T cells into aTregs, the activated subset of regulatory T cells and are essential in maintaining immune tolerance and immune homeostasis, especially in those with AR (30). Recently, Burleson et al (43) established that HDM-challenged TET1-deficient mice have impaired interferon pathway, increased airway hyperresponsiveness, and eosinophilic infiltration in the lung. Together, this evidence suggests that the loss of TET1 induces the maturation of DCs and mediates the development of allergic airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution has notably been shown to have a direct influence on the expression of enzymes involved in the balance of DNA methylation and demethylation through increasing DNA methylation levels at the promoter of the DNA demethylating enzyme TET1 [60]. Recent data in a mouse model deficient for Tet1 supports an important role for this enzyme in airway disease leading to increased expression of Th1 and Th2 cytokines, lung eosinophilia and airway hyperresponsiveness, which were at least partially mediated by a genome-wide hypermethylation including genes involved in interferon signaling [61]. Furthermore, air pollution has also shown to alter the expression profile of miRNAs involved in inflammation and which have also been associated with allergic diseases [52,62].…”
Section: Environment and Epigenetics In Asthma And Allergymentioning
confidence: 99%
“…Subsequently, we recently showed that Tet1 inhibits asthma-related phenotypes including airway hyperresponsiveness (AHR) and lung eosinophilia in mice. 44 In this HDM-induced allergic airway model, we found that Tet1, Tet2, and Tet3 were downregulated while Dnmt1, Dnmt3a, and Dnmt3b remain unchanged following the last intratracheal instillation of HDM. These changes in DNA methylation machinery are associated with DNA methylation changes in pathways such as Epithelial Adherens Junction Signaling and Leukocyte Extravasation Signaling (Zhang X and Ji H, unpublished data).…”
Section: Environmental Epigenetics and Tet1mentioning
confidence: 66%
“…22 Meanwhile, our studies in human bronchial epithelial cells (HBECs) suggest that TET1 may interact with histone modification enzymes EZH2 and transcription factors to regulate expression of genes in the interferon signaling pathway. 44…”
Section: Function Of Tet1mentioning
confidence: 99%
See 1 more Smart Citation